Preliminary Validation of Digital Photography to Assess the Home Food Environment - Daniela Quan; Isaac Michael; Elizabeth Gollub (MDPI AG, 2023)
The home food environment (HFE), the availability and accessibility of foods and food products within the home, has a strong influence on healthy eating behaviors. Studies assessing the HFE commonly utilize a home food inventory (HFI) for data collection. However, this approach tends to be burdensome for participants. This study validated a low-burden digital photo method for assessing the home food environment and confirmed that this method is preferred by participants. Study participants completed an HFI, submitted photos of household foods, then identified preference for the HFI or photo reporting method. Researchers completed an HFI based on each participant's photo submissions. Researcher-to-participant and researcher-to-researcher comparisons were made through ANOVA and randomized block analyses to determine concurrent validity and inter-rater reliability. Method preference was assessed using the Z-test. The participant group (N = 53) was predominantly female (68%), young adult (90.5%), and Hispanic or Latino (71.7%). Concurrent validity was initially moderate (ĸ = 0.54); adjustments yielded substantial agreement (ĸ = 0.61). The inter-rater reliability (p = 0.98) demonstrated significant consistency among reviewers. The photo-documentation method was found to be valid and preferred (p = 0.01) for reporting on the HFE. The photo method can be used advantageously to collect quality data.